ANALISIS KINERJA KANTOR PELAYANAN PENYULUHAN DAN KONSULTASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris di KP2KP Padangpanjang) - Yuskar .; Resi Amelia (Jurnal Riset AKuntansi dan Bisnis, 2014)
The objective of this research are to analyze and find out the effect of performance of tax office which is consist of indicator varibel productivity, responsiveness, quality of service, responsibility and accountability to tax compliance of tax payer. This is the emperical study in tax office of Padangpanjang. The research data was obtained through questionnaire with 60 respondent involves taxpayers in tax office of  Padangpanjang. Sample taken by purposive sampling. The method of data analysis used is doubled regression. The result of research show that partially, only indicator responsibility have effect on tax compliance. The analysis show that together, independent varibels have a significant simultaneous effect to tax compliance of taxpayer at tax office of Padangpanjang.